2011
DOI: 10.1186/1471-2350-12-168
|View full text |Cite
|
Sign up to set email alerts
|

"Single nucleotide polymorphisms of the OPG/RANKL system genes in primary hyperparathyroidism and their relationship with bone mineral density"

Abstract: BackgroundPrimary hyperparathyroidism (PHPT) affects mainly cortical bone. It is thought that parathyroid hormone (PTH) indirectly regulates the activity of osteoclasts by means of the osteoprotegerin/ligand of the receptor activator of nuclear factor-κβ (OPG/RANKL) system. Several studies have confirmed that OPG (osteoprotegerin) and RANKL (ligand of the receptor activator of nuclear factor-κβ) loci are determinants of bone mineral density (BMD) in the general population. The aim of this study is to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
3
20
1
3
Order By: Relevance
“…In detail, concerning the rs3102735 SNP the G allele was more common among fracture patients [28,34] and patients with lower BMD at the distal radius [30]. Furthermore, there is an association within a subgroup of postmenopausal patients carrying the minor allele and a lower calcaneal velocity of sound [36].…”
Section: Discussionmentioning
confidence: 99%
“…In detail, concerning the rs3102735 SNP the G allele was more common among fracture patients [28,34] and patients with lower BMD at the distal radius [30]. Furthermore, there is an association within a subgroup of postmenopausal patients carrying the minor allele and a lower calcaneal velocity of sound [36].…”
Section: Discussionmentioning
confidence: 99%
“…To check the quality of the genotyping, 30 random samples (8.2 %) were analyzed twice [16], and the results showed a 98 % concordance. Discordant samples were analyzed three times, and concordant results are presented.…”
Section: Snp Genotypingmentioning
confidence: 99%
“…The RANKL 290 A>G, OPG 1181 G>C, 245 T>G, and 163 A>G and RANK A>G SNPs were chosen because they are the SNPs most frequently cited in the literature as being associated with decreased BMD and increased fractures [9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the high bone turnover observed in our patients. This fact has been observed by other authors [11][12][13]. The key role of RANKL was demonstrated by Nakchbadi et al [14], who found an increase in RANKL in patients with HPT that correlated with resorption markers.…”
Section: Discussionmentioning
confidence: 54%